First-person shooter gaming simulator / Tajmalludin Yaakob - Yaakob, Tajmalludin (2013)
In this paperwork, I have developed a device that worked with first-person shooter (FPS) game tbr personal computer (PC) platform. The idea of this project is to change the way of playing the FPS game from using the conventional method; mouse and keyboard to the real weapon model. This project uses the Arduino Due as the microcontroller and the accelerometer ADXL 335 as the main subject besides joystick and push button as parts of the components.